PERAN KEKUASAAN DAN POLITIK KEPALA SEKOLAH DI SMP NEGERI 7 PEMALANG - Teguh Gunarso; Turiyah; Noor Miyono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to examine the role of school principals' power and politics in educational management at SMP Negeri 7 Pemalang. This research uses a qualitative approach with a case study method to explore in depth the dynamics of power and politics that exist in school principal policies which influence the learning process, relationships between employees, and decision making in schools. Data collection techniques are carried out through interviews, observation and documentation involving school principals, teachers, administrative staff and other related parties. The research results show that school principals have a strong influence in determining policies, both in academic and non-academic aspects. However, the power they have often interacts with internal politics involving various groups in schools, which affects the effectiveness of implementing these policies. Internal conflicts that arise are often related to personal and group interests, which sometimes affect the quality of work and professional relationships at school. These findings provide an important picture of how politics and power within schools can influence educational performance and development at the junior high school level, as well as the importance of wise leadership strategies in facing these challenges.